Study the Relationship of Earthquake and Ionosphere Using IRI TEC for Education - Nawaphon Phansori; Sirinil Phukrongta; Onuma Kriamthaisong; Prasert Kenpankho (Universitas Pendidikan Indonesia (UPI), 2022)
This research is aimed to study and analyze the relationship between the earthquake events and the disturbance of ionosphere. The method is by using the International Reference Ionosphere (IRI) model to get Total Electron Content (TEC) values and then find the correlation on earthquake events and ionosphere. The result is to be correlated at 0.056, which shows the evidence of correlationon earthquake events and ionosphere. For the future work, we will study the significant on the development of earthquake warning system. This study can be used for educational purposes.